The burden of neurological disorders across the states of India: the Global Burden of Disease Study 1990–2019. Issue 8 (August 2021) - ,; Singh, Gagandeep; Sharma, Meenakshi; Kumar, G Anil; Rao, N Girish; Prasad, Kameshwar; Mathur, Prashant; Pandian, Jeyaraj D; Steinmetz, Jaimie D; Biswas, Atanu; Pal, Pramod K; Prakash, Sanjay; et al.
Summary: Background: A systematic understanding of the burden of neurological disorders at the subnational level is not readily available for India. We present a comprehensive analysis of the disease burden and trends of neurological disorders at the state level in India. Methods: Using all accessible data from multiple sources, we estimated the prevalence or incidence and disability-adjusted life-years (DALYs) for neurological disorders from 1990 to 2019 for all states of India as part of the Global Burden of Diseases, Injuries, and Risk Factors Study 2019. We assessed the contribution of each neurological disorder to deaths and DALYs in India in 2019, their trends in prevalence or incidence and DALY rates over time, and heterogeneity between the states of India. We also assessed the Pearson correlation coefficient between Socio-demographic Index (SDI) of the states and the prevalence or incidence and DALY rates of each neurological disorder. Additionally, we estimated the contribution of known risk factors to DALYs from neurological disorders. We calculated 95% uncertainty intervals (UIs) for the mean estimates. Findings: The contribution of non-communicable neurological disorders to total DALYs in India doubled from 4·0% (95% UI 3·2–5·0) in 1990 to 8·2% (6·6–10·2) in 2019, and the contribution of injury-related neurological disorders increased from 0·2% (0·2–0·3) to 0·6% (0·5–0·7). Conversely, the contribution of communicable neurological disorders decreased from 4·1% (3·5–4·8) to 1·1% (0·9–1·5) during the same period. In 2019, the largest contributors to the total neurological disorder DALYs in India were stroke (37·9% [29·9–46·1]), headache disorders (17·5% [3·6–32·5]), epilepsy (11·3% [9·0–14·3]), cerebral palsy (5·7% [4·2–7·7]), and encephalitis (5·3% [3·7–8·9]). The crude DALY rate of several neurological disorders had considerable heterogeneity between the states in 2019, with the highest variation for tetanus (93·2 times), meningitis (8·3 times), and stroke (5·5 times). SDI of the states had a moderate significant negative correlation with communicable neurological disorder DALY rate and a moderate significant positive correlation with injury-related neurological disorder DALY rate in 2019. For most of the non-communicable neurological disorders, there was an increase in prevalence or incidence from 1990 to 2019. Substantial decreases were evident in the incidence and DALY rates of communicable neurological disorders during the same period. Migraine and multiple sclerosis were more prevalent among females than males and traumatic brain injuries were more common among males than females in 2019. Communicable diseases contributed to the majority of total neurological disorder DALYs in children younger than 5 years, and non-communicable neurological disorders were the highest contributor in all other age groups. In 2019, the leading risk factors contributing to DALYs due to non-communicable neurological disorders in India included high systolic blood pressure, air pollution, dietary risks, high fasting plasma glucose, and high body-mass index. For communicable disorders, the identified risk factors with modest contributions to DALYs were low birthweight and short gestation and air pollution. Interpretation: The increasing contribution of non-communicable and injury-related neurological disorders to the overall disease burden in India, and the substantial state-level variation in the burden of many neurological disorders highlight the need for state-specific health system responses to address the gaps in neurology services related to awareness, early identification, treatment, and rehabilitation. Funding: Bill & Melinda Gates Foundation; and Indian Council of Medical Research, Department of Health Research, Ministry of Health and Family Welfare, Government of India.